2014
DOI: 10.1037/a0035288
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy as a predictor of self-reported physical, cognitive, and social functioning in multiple sclerosis.

Abstract: Objective Investigate whether self-efficacy is associated with physical, cognitive and social functioning in individuals with Multiple Sclerosis (MS) when controlling for disease-related characteristics and depressive symptomatology. Participants 81 individuals between the ages of 29 and 67 with a diagnosis of clinically definite MS. Method Hierarchical regression analysis was employed to examine the relationships between self-efficacy and self-reported physical, cognitive, and social functioning. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 60 publications
10
43
0
1
Order By: Relevance
“…The finding that as perceived deficits increase so do feelings of depression, is consistent with other studies, 4,6,7,8 suggesting that self-reported cognitive difficulties are related to depressive symptoms. Importantly, these are correlations that demonstrate associations not causality.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The finding that as perceived deficits increase so do feelings of depression, is consistent with other studies, 4,6,7,8 suggesting that self-reported cognitive difficulties are related to depressive symptoms. Importantly, these are correlations that demonstrate associations not causality.…”
Section: Discussionsupporting
confidence: 91%
“…6,7,8,22,23 The PDQ total score reported in this sample was similar to previously reported findings 6,8,22 and lower than the means in two studies, by approximately 5- 16 points. 7,23 The results of this analysis support the internal consistency reliability of the PDQ total scale.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…26 A more recent investigation found selfefficacy to be a significant predictor of physical, social, and cognitive functioning in MS, even when taking into account neurologic impairment and depression. 34 Low self-efficacy has also been shown to be related to high levels of depression. 25 Depression and low self-efficacy accompanied by increased stress and disability tend to result in a greater chance of developing anxiety in individuals with MS. 35 Taken together, it may be proposed that reduced self-efficacy lies at the root of the psychological distress found in MS, which could result in problems with adjustment, perception, and management of one's illness.…”
Section: Discussionmentioning
confidence: 99%